Pengaruh Pola Asuh Orangtua Dan Lingkungan Sekolah Terhadap Karakter Anak Didik SMA Dharma Bakti Siborongborong - Sihombing, Grace Metaria (LPPM-Institut Agama kristen Negeri Tarutung, 2024)
The objectives of this study are: 1) to determine the effect of parenting on the character of students at Dharma Bakti Siborongborong High School; 2) to explore how the school environment affects student character; and 3) to evaluate the combined influence of parenting and school environment on student character. The research utilized a quantitative method with a positivistic approach. The population was 165 students, with a sample of 113 selected using the Krejcie table. Data were collected via a closed questionnaire consisting of 139 items. The results showed that: 1) parenting has a positive and significant effect on student character at 31.4%; 2) the school environment positively and significantly influences student character at 22.7%; and 3) the combined effect of parenting and school environment on student character is 33.9%. Hypothesis testing confirmed that Ha is accepted and H0 is rejected.